2018
DOI: 10.1016/j.ajhg.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association of Albuminuria with Cardiometabolic Disease and Blood Pressure

Abstract: Excretion of albumin in urine, or albuminuria, is associated with the development of multiple cardiovascular and metabolic diseases. However, whether pathways leading to albuminuria are causal for cardiometabolic diseases is unclear. We addressed this question using a Mendelian randomization framework in the UK Biobank, a large population-based cohort. We first performed a genome-wide association study for albuminuria in 382,500 individuals and identified 32 new albuminuria loci. We constructed albuminuria gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
96
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 76 publications
9
96
0
4
Order By: Relevance
“…Regarding albumin and blood pressure, our results are consistent with a recent previous study 15 which supported the existence of a bidirectional causal association between albuminuria and blood pressure.…”
Section: Comparison With Prior Observational Studiessupporting
confidence: 92%
See 3 more Smart Citations
“…Regarding albumin and blood pressure, our results are consistent with a recent previous study 15 which supported the existence of a bidirectional causal association between albuminuria and blood pressure.…”
Section: Comparison With Prior Observational Studiessupporting
confidence: 92%
“…Our results are consistent with previous literature which reported that high albumin is associated with higher susceptibility to CVD 13 and hypertension. 15 Previous studies have shown inconsistent results between sodium intake and the risk of CVD. The Scottish Heart Study, a population-based longitudinal study of 10,000 people, showed no consistent associations between sodium intake and cardiovascular or all-cause mortality.…”
Section: Comparison With Prior Observational Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…We also leveraged summary statistics manually downloaded from recent large association studies for Chronic Kidney Disease 39 , blood lipids 40 , Atrial Fibrillation, Type-II Diabetes, Coronary Artery Disease, estimated glomerular filtration rate 41 , albuminuria 42 , and anthropometric traits 43 . Two proteins, PDL2 and TNFRSF10C, had both cis and trans associations where the trans did not fall in a highly pleiotropic gene.…”
Section: Two-sample Mrmentioning
confidence: 99%